A climate stress testing exercise on loans to European small and medium enterprises - Yujia Chen; Zhenghong Ding; Luca Barbaglia; Raffaella Calabrese; Serena Fatica (European Commission, 2025)
This paper assesses the impact of floods on credit to European small and medium-sized enterprises (SMEs) using a discrete-time survival model. We find a statistically significant relationship between the default probability of loans to SMEs and floods occurring in the region where the firm is located. We propose a micro-level stress testing exercise to assess the performance of small business loans under different climate scenarios. This approach enables the identification of European regions that exhibit heightened vulnerability under adverse climate scenarios. It also allows financial institutions and regulators to quantify the increase in default probability for each loan.
Keywords: C55; G21; Q51; Q54; 330; climate change; loan default; natural disasters; risk modelling; stress testing